Legal Protection of Protected Animals from Illegal Trade as an Effort to Maintain Environmental Conservation - ETIKA, TAKARIADINDA DIANA; RAHARJA, SUNARYA; HARTANTI; SULISTYANINGSIH, ENDANG; WIDYATAMA, YUSA PUTRA; TAMTAMA, ARGA SYA’BAN (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The research entitled "Legal Protection of Protected Animals from Illegal Trade as an Effort to Maintain Environmental Conservation" aims to 1) find out and analyze legal protection for protected animals from illegal trade as an effort to preserve the environment. 2) analyze the execution process carried out towards  the judge's decision regarding illegal animal trade. The research method used is normative legal research, using a juridical approach, primary data obtained from interviews with secondary legal materials (books and other related literature), and tertiary legal materials (internet), data collection techniques in the form of interviews and literature studies, and Data analysis is in the form of qualitative descriptive. Based on the results of the research and discussion, it was concluded that 1) efforts to legally protect protected animals are not only through enforcing applicable laws and regulations, but can also be done through approaches and raising awareness in  Special Region of Yogyakarta citizen through outreaching activities and information about the importance of preserving animals and understand the types of animals that are protected. 2) the process of executing the judge's decision regarding illegal animal trade is different from that of human victims because it requires special treatment, especially for animals that are still alive, by handing over protected animals to the Natural Resources Conservation Center  Special Region of Yogyakarta for care and restoration of their condition before being returned to their habitat.